Are parental self‐efficacy and family flexibility mediators of treatment for anorexia nervosa?. Issue 3 (4th January 2018) - Sadeh‐Sharvit, Shiri; Arnow, Katherine D.; Osipov, Lilya; Lock, James D.; Jo, Booil; Pajarito, Sarah; Brandt, Harry; Dodge, Elizabeth; Halmi, Katherine A.; Johnson, Craig; Kaye, Walter; Wilfley, Denise; et al.
Abstract: Objective: Family‐based treatment (FBT) for adolescent anorexia nervosa (AN) promotes faster weight restoration when compared to other treatments. However, the mechanisms through which this occurs are not clarified. This study explored the trajectories of parental self‐efficacy and perceived family flexibility during FBT and systemic family therapy (SyFT). We also explored whether parental self‐efficacy mediates the effects of treatment on weight gain early in treatment. Method: 158 adolescents (12–18 years old; 89% girls) and their parents were randomized to FBT or SyFT. Parental self‐efficacy as well as adolescents' and parental perceptions of the family's flexibility were collected at baseline and at sessions 2, 4, 6, and 8. Results: Over time, only parents in FBT reported significantly greater self‐efficacy. The change in maternal self‐efficacy over the first 8 weeks of treatment was a significant mediator of session 10 weight gain. There were no significant group differences in perceived flexibility by session 8. Discussion: Both parents in FBT and mothers in SyFT understand early the need to change their family's rules and roles. However, the specific strategies of FBT appear to mediate early weight gain in AN.